The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/bies.20575
|View full text |Cite
|
Sign up to set email alerts
|

Redox rhythmicity: clocks at the core of temporal coherence

Abstract: Ultradian rhythms are those that cycle many times in a day and are therefore measured in hours, minutes, seconds or even fractions of a second. In yeasts and protists, a temperature-compensated clock with a period of about an hour (30-90 minutes) provides the time base upon which all central processes are synchronized. A 40-minute clock in yeast times metabolic, respiratory and transcriptional processes, and controls cell division cycle progression. This system has at its core a redox cycle involving NAD(P)H a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 83 publications
3
63
0
Order By: Relevance
“…It was suggested that oxidative stress acts as a trigger for H 2 S production, which itself acts as a redox regulator when the level of oxidative stress exceeds the antioxidant capacity of the cell. (87)(88)(89) This tight relationship suggests that the origin of mitochondrial endosymbionts may be based on a syntrophic association between a sulphide-oxidizing aproteobacterium and an archaeal sulphide-producing host.…”
Section: The Driving Force For Endosymbiosismentioning
confidence: 95%
“…It was suggested that oxidative stress acts as a trigger for H 2 S production, which itself acts as a redox regulator when the level of oxidative stress exceeds the antioxidant capacity of the cell. (87)(88)(89) This tight relationship suggests that the origin of mitochondrial endosymbionts may be based on a syntrophic association between a sulphide-oxidizing aproteobacterium and an archaeal sulphide-producing host.…”
Section: The Driving Force For Endosymbiosismentioning
confidence: 95%
“…Subsequent research has further elaborated on these oscillations and their functions. For example, in brewer's yeast, Lloyd and Murray (2007) identified oscillations between oxidative and reductive phases over approximately 40 minutes, which they construed as a major regulator of cellular activity: processes such as cell division and gene expression are limited to the reductive phase, when DNA will not be damaged by free oxygen that would be available in the oxidative phase.…”
Section: Endogenous Oscillatory Activity In Biological Mechanismsmentioning
confidence: 99%
“…We only have to think, for example, of the temporal scale of energy generation, metabolic reactions, transcriptional order, and cell proliferation and development. All these processes make evident the presence and ubiquity of ultradian oscillators in biology: with a period of about 40 minutes, the oxygen consumption and other metabolic processes in Acanthamoeba castellanii; similar ultradian clocks were observed in other protists (ciliates and flagellates) and yeast; a 40 minute cycle in general transcriptional activity in yeast; with a period of 69 minutes, respiration in Dictyostelium; 3 hour cycles of expression of the mammalian p53 protein; 2 hour periodicity in the expression of the Notch effector Hes1 in cultured cells; a 1.5-3 hour periodicity in the expression of NF-κB signaling molecule in mouse cells in culture, among many others (Lloyd & Murray, 2007;Paetkau et al, 2006). The complex time structure of organisms requires the synchronized operation of multiple processes in many time domains.…”
Section: The Oscillation In the Circadian Pacemaker By Coupling Ultramentioning
confidence: 89%